Experimental and Numerical Analysis of Omnidirectional Steel Moment Connection With Through-Plate Panel Zone Under Cyclic Loading - Hadi Askarian; Mohammad Reza Sohrabi; Seyed Morteza Kazemi (Shock and Vibration)
This paper proposes a new beam to column connection, namely, the omnidirectional steel moment connection with through-plate panel zone, which enables the connection of more than four beams to a column in moment frames at any arbitrary angle. The proposed connection was experimentally and numerically analyzed under cyclic loading. A numerical model using finite element method in ABAQUS is created and validated using hysteretic moment-rotation curves. Subsequently, a sensitivity analysis is conducted on the key components of the proposed connection, including the connection panel zone, web plate, and bolts. The aim of this study is to optimize the design and configuration of the connection panel zone by simplifying it and removing the intersection of the through plates. Furthermore, the effect of changing the axial load of the column, removing the web plate, and altering the bolt size on the connection panel zone is investigated. The results of this sensitivity analysis demonstrate the efficiency and effectiveness of the proposed designs. The findings indicated that the experimental specimen showcased remarkable seismic compliance, adhering to AISC seismic provisions for special moment frames, even with minor buckling. It sustained a 0.04 radians drift without brittle fracture, aligning with expected mechanical behavior. The finite element-based model revealed stress concentrations at beam-to-plate connections, and the average difference between the experimental and numerical model was 11.82%, verifying model accuracy. Hexagonal prism panels and internal through plates contribute minimally to parameter variations. In contrast, the web shear plate significantly affects the behavior. Bolt material substitution and axial loading introduce significant changes, while the combined effect of axial load and hexagonal prism panel removal shows distinctive alterations.